Recovery of Salmonella Enteritidis and Campylobacter coli injected into hatching eggs that are cold-stored and incubated through day 18 of incubation - C.E. Harris; L.N.B. Josselson; R.J. Buhr (Journal of Applied Poultry Research, 2023)
SUMMARY: Salmonella and Campylobacter spp. are important foodborne pathogens of concern. Both horizontal and vertical transmission of Salmonella into poultry flocks is well documented to occur, whereas only horizontal transmission of Campylobacter has been confirmed. The objective of this study was to evaluate the ability of Salmonella and Campylobacter to translocate from egg contents into the embryo during incubation. Three experiments were performed comparing Salmonella recovery from eggs that were cold-stored (48 h) and incubated up to D15 or D18 of incubation. Four experiments were performed comparing Campylobacter recovery from eggs that were cold-stored and incubated up to D15 or D18 of incubation. Eggs were injected with 102-3 CFU Salmonella Enteritidis or 103 CFU Campylobacter coli into the albumen or yolk, and sampling of the egg contents and viable embryos was performed periodically during cold-storage and incubation. In the Salmonella experiments, egg contents from yolk injected eggs sampled during incubation were 100% positive, and no viable embryos were present. In contrast, Salmonella albumen injected eggs sampled on D18 had 51% positive egg contents and 37% positive embryos. In the Campylobacter experiments, 15% of embryos of yolk injected eggs were positive at D15, but no egg contents or embryos were positive at D18 of incubation. Results indicate that the albumen is likely to be the site for contamination than the yolk for forming eggs resulting in Salmonella positive embryos. Additionally, Campylobacter vertical transmission appears to be unlikely, but if it does occur, the location of the contamination is more likely the yolk contents.